84.4k views
3 votes
By letting y = x^1/3, or otherwise, find the values of x for which x^1/3 -2x^-1/3 = 1

User Trajectory
by
5.1k points

1 Answer

4 votes

In this case, the problem is asking us to solve the equation


x^{(1)/(3)} - \frac{2}{x^{(1)/(3)}} = 1

by substituting
y = x^{(1)/(3)}.


First, let's substitute the variable into the original equation:


y - (2)/(y) = 1


Now, let's solve:


y - (2)/(y) = 1

  • Set up


y\Bigg(y - (2)/(y)\Bigg) = y(1) \Rightarrow y^2 - 2 = y

  • Multiply the entire equation by
    y to remove the fraction over
    y


y^2 - y - 2 = 0

  • Subtract
    y from both sides of the equation for easier factoring


(y - 2)(y + 1) = 0

  • Factor


y - 2 = 0 \,\, \textrm{and} \,\, y + 1 = 0

  • Solve the factored equation using the Zero Product Property


y = 2, -1

  • Solve each equation

Now, we aren't done yet. We have to find our answer in terms of the original variable,
x. To do this, set each value for
y into the substitution equation we found earlier,
y = x^{(1)/(3)}:


2 = x^{(1)/(3)}


2^3 = x


x = 8


-1 = x^{(1)/(3)}


(-1)^3 = x


x = -1


The solutions for the equation are x = -1, 8.

User Luca Guidi
by
5.1k points